Determination of common HIV-1 cytotoxic T lymphocytes epitopes across different ethnicities for their potencial use as immunological therapy in Colombia. (2011)
Cytotoxic T lymphocytes (CTL) recognition of antigenic peptides (epitopes) presented by HLA class I molecules is critical for the immunity against HIV infection. The identification of CTL epitopes against HIV is complicated by several factors. 1) limited knowledge about the mechanisms involved in the generation of CTL epitopes; 2) more than 1,700 different HLA-I molecules described to date, each one capable of presenting different CTL epitopes; 3) variable distribution of HLA genes in different ethnicities making impossible to identify common CTL epitopes for all patients of a single nationality. The problem of variable distribution of HLA genes for CTL identification is particularly critical in Colombia, given the wide distribution of HIV infection among several ethnicities, including 70% Caucasoids, 15% Amerindians and 15% African descendents. The specific hypothesis of this project is that several HLA class I molecules, classified in groups known as HLA supertypes, can bind large overlapping sets of peptides from HIV and that the identification of common CTL epitopes could be used for immunological therapy against HIV in patients from all ethnicities found in Colombia.